(untitled) (Global Journal of Management and Business Research, 2020)
More often than not, professionals are rated by ethical values in addition to their field of speciality most especially when its on finances and management. Eventually that suggest further investigation on ethical values in correlation with the education in accounting field of study, hence this study. Determinants and adequacy of ethical education provided to students of accounting on ethical values in Southwestern Nigeria were investigated. The study also evaluated the influence of ethics education on perception of students of accounting on ethical values with the view to providing necessary and useful output in educational policy making, and developments. Data were sourced with the use of structured questionnaire on four hundred (400) students as respondents drawn from among final year students of Federal, State and Private higher institutions from a population of about One Thousan and Ninet Three (1093) respondents in tertiary institutions in Southwestern Nigeria.